Transforming Library Services: Social and Technological Factors Shaping Digital Adoption among Young Users - Zainal Abidin; Ahmad Qusairi; Fadhel Mubarak (Program Studi Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2025)
This study aims to identify the key social and technological factors influencing the adoption of digital library services among young users and to formulate innovative strategies that enhance library attractiveness in the digital era. A quantitative approach was employed, using multiple linear regression analysis of survey data collected from 210 respondents across several urban public and academic libraries, complemented by 20 semi-structured interviews with active users and library managers. Data were processed with SPSS to examine the effects of perceived usefulness, ease of use, social norms, and environmental support on digital service adoption. The findings indicate that perceived benefits (β=0.42, p<0.01) and ease of use (β=0.35, p<0.01) significantly influence user interest in adopting digital services, while social norms and environmental support (β=0.25, p<0.05) also play important reinforcing roles. Conversely, factors such as self-confidence and perceived risks show weaker effects, suggesting the need for further psychological exploration. Interview data highlight that interactive features, active promotion, and user-friendly interfaces are crucial in shaping positive experiences and increasing adoption. The study strengthens the Technology Acceptance Model (TAM) with psychosocial perspectives and provides practical strategies for adaptive, user-oriented, and culturally relevant library services. Future initiatives should expand research into rural libraries and integrate cultural variables to ensure inclusive and sustainable digital transformation strategies.